2018
DOI: 10.22209/ic.v59n3a06
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the biochemical, haemostatic and toxinological aspects of mapanare dry-tail (Porthidium lansbergii rozei) snake´s venom causing human accidents in Eastern Venezuela

Abstract: Porthidium lansbergii rozei (P.l.rozei) is a snake species belonging to the Venezuelan ophidian-fauna causing relatively frequent human accidents. This study has been developed to enrich the medical information about this snake´s accident, which is often handled with difficulties due to the ignorance about its toxic activities. This work has studied the biochemical and toxinological characteristics of the P.l.rozei venom. The objective was to determine its biochemical characteristics, including protein content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In the particular cases of A. bilineatus and C. basiliscus where EDTA treatment does not modify the proteolysis of fibrinogen, it can be concluded that SVMPs are not involved in the degradation of this protein, and it is suggested that SVSPs are responsible. A contrasting scenario occurs with the venoms of O. sphenophrys and P. yucatanicum, where the digestion of the α and β chains is catalyzed mainly by SVMPs, which agrees with what has been reported for the venom of P. lansbergii rozei [54]. It is also worth mentioning that the degradation of the γ chain caused by M. nummifer venom is caused by SVMPs since the presence of EDTA inhibited it (Table 5).…”
Section: Proteolytic Activity On Azocaseinsupporting
confidence: 84%
See 2 more Smart Citations
“…In the particular cases of A. bilineatus and C. basiliscus where EDTA treatment does not modify the proteolysis of fibrinogen, it can be concluded that SVMPs are not involved in the degradation of this protein, and it is suggested that SVSPs are responsible. A contrasting scenario occurs with the venoms of O. sphenophrys and P. yucatanicum, where the digestion of the α and β chains is catalyzed mainly by SVMPs, which agrees with what has been reported for the venom of P. lansbergii rozei [54]. It is also worth mentioning that the degradation of the γ chain caused by M. nummifer venom is caused by SVMPs since the presence of EDTA inhibited it (Table 5).…”
Section: Proteolytic Activity On Azocaseinsupporting
confidence: 84%
“…yucatanicum , where the digestion of the α and β chains is catalyzed mainly by SVMPs, which agrees with what has been reported for the venom of P . lansbergii rozei [ 54 ]. It is also worth mentioning that the degradation of the ɣ chain caused by M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation